Characterization of Phosphate Glass Reinforced Gelatin Blend Bioactive Composite Films - Dey, Kamol; Alamgir, Poonam; Parvin, Shahnaz; Mohol, Gulshana; Tonny, Wafa; Khan, Mubarak A.; Khan, Ruhul A. (Journal of Research Updates in Polymer Science, 2014)
Bioactive composite films were prepared using bioresorbable phosphate glass powder and biodegradable polymer gelatin (G) through solution casting process. Biocompatible monomer, 2-hydroxyethyl methacrylate (HEMA) was used as the cross-linking agent and bioresorbable phosphate glass (PG) powder was used as reinforcement filler. The composite films were obtained at various ratios of G, PG and HEMA. The PG modified gelatin composite (PG/G) film was fabricated at a weight ratio of 12:88 while HEMA modified gelatin composite (HEMA/G) film at 50:50 ratio. On the other hand, hybrid gelatin composite film, containing both PG and HEMA, was obtained using a G/PG/HEMA ratio of 44:12:44. Incorporation of PG improved the mechanical properties of the composite films. Morphological property of the composite films was investigated by stereo microscope and it revealed that the composite films were porous in nature. The thermal behaviour of the films was studied using thermogravimetric analysis. Water uptake of the films was also performed.